Cost‐Utility Analysis of Routine Anxiety and Depression Screening in Patients Consulting for Osteoarthritis: Results From a Clinical, Randomized Controlled Trial. Issue 12 (28th November 2018) - Kigozi, Jesse; Jowett, Sue; Nicholl, Barbara I.; Lewis, Martyn; Bartlam, Bernadette; Green, Daniel; Belcher, John; Clarkson, Kris; Lingard, Zoe; Pope, Christopher; Chew‐Graham, Carolyn A.; Croft, Peter; et al.
Abstract : Objective: To investigate the cost‐effectiveness (cost‐utility) of introducing general practitioner screening for anxiety and depression in patients consulting for osteoarthritis (OA). Methods: A cluster‐randomized trial‐based economic evaluation to assess general practitioners screening for anxiety and depression symptoms in patients consulting for OA compared to usual care (screening for pain intensity) was undertaken over a 12‐month period from a UK National Health Service and societal perspective. Patient‐level mean costs and mean quality‐adjusted life years (QALYs) were estimated, and cost‐effectiveness acceptability curves controlling for cluster‐level data were constructed. The base‐case analysis used the net benefit regressions approach. The 2‐stage nonparametric sampling technique was explored in a sensitivity analysis. Results: The base‐case analysis demonstrated that the intervention was as costly as, and less effective than, the control (QALY differential −0.029 [95% confidence interval −0.062, 0.003]). In the base‐case analyses, general practitioner screening for anxiety and depression was unlikely to be a cost‐effective option (probability <5% at £20, 000/QALY). Similar results were observed in all sensitivity analyses. Conclusion: Prompting general practitioners to routinely screen and manage comorbid anxiety and depression in patients presenting with OA is unlikely to be cost‐effective. Further research is needed to explore clinically effective and cost‐effective models of managing anxiety and depression in patients presenting with clinical OA.